Experimental and theoretical studies for mild steel corrosion inhibition in 1.0M HCl by three new quinoxalinone derivatives - Tazouti, A.; Galai, M.; Touir, R.; Touhami, M. Ebn; Zarrouk, A.; Ramli, Y.; Saracoglu, M.; Kaya, S.; Kandemirli, F.; Kaya, C. (Elsevier BV, 2016)
Abstract Three quinoxalinone derivatives, namely (E)-3-styrylquinoxalin-2(1H)-one (SQ), (E)-3-(4-methoxystyryl)quinoxalin-2(1H)-one (MOSQ) and (E)-3-(4-methoxystyryl)-7-methylquinoxalin-2(1H)-one (MOSMQ) were synthesized and characterized. Thus, their inhibition effects on mild steel corrosion in 1.0 M HCl medium were investigated using weight loss method, electrochemical measurements. The effect of temperature on the corrosion behavior of mild steel was studied in the range of 298–328 K. Polarization measurements indicated that, the studied compounds act as a mixed type inhibitors, the inhibition efficiency depends on their concentrations and followed the order MOSQ > MOSMQ > SQ. Electrochemical impedance spectroscopy showed that all compounds act by the formation of a protective film at the metallic surface. The adsorption of three inhibitors on steel surface obeyed Langmuir model, thus the thermodynamic and kinetic parameters were calculated and discussed. In the part based on DFT calculations of this study, some electronic properties of studied molecules were calculated and discussed with the help of B3LYP/6-311G (d,p), B3LYP/6-311 ++G (d,p) and B3LYP/6-311G ++ (2d,2p) methods. The theoretical and experimental results are in good agreement.
Keywords: Mild steel; Computational chemistry; Quinoxalinone derivatives; Corrosion inhibition; Electrochemical techniques; 0 M HCl